PENGARUH PRAKTIK SOCIAL NETWORKING, KEPERCAYAAN MEREK DAN LOYALITAS MEREK PADA KOMUNITAS MEREK ONLINE - Futuwwah, Ali Imaduddin; Mardhiyah, Dien (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
The development of the internet made the brand community move to online activities by using a social media chat group platform. This study aims to examine the relationship between social networking and brand trust on brand loyalty in the online brand community. Data were collected through a questionnaire of 150 respondents. Through SEM analysis (PLS), the results show that social networking has a positive effect on brand trust and trust mediates the relationship between social networking and brand. This finding implies that the brand community must pay attention to social networking activities that can increase brand trust and brand loyalty. Companies and communities need to think about how to develop strong relationships and bonds between members so that members feel the value of the brand and build a strong commitment with the brand. Key words: Online-based brand community, social networking, brand trust, brand loyalty, partial least square